VOICES IN SHAPING THE SUBJECTIVITY OF PEDAGOGICAL CONTENT KNOWLEDGE - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2008)
In this paper we. consider pedagogical content knowledge as involving subjective decisions on making the content instructional and are concerned with the development of this subjectivity. In our attempts to understand how pre-service teachers decide upon what approach is the best in delivering the mathematical content we find Bakhtinian concept of voice useful. Our examination of the pre-service teachers' microteachings and retrospective interviews suggests that teacher candidates' discourse and practice were greatly shaped by the voices of others who are distant in space and time. These voices are selectively assimilated and this assimilation reflects certain value judgements. We exemplify our arguments with a pre-service teacher's introduction of derivative during a microteaching activity.
Keywords: REFORM